Gamification with self-determination theory to foster intercultural communicative competence and intrinsic motivation - Min, Su; Azean Atan, Noor; Habibi, Akhmad (International Journal of Evaluation and Research in Education (IJERE), 2025)
In globalization, possessing intercultural communicative competence (ICC) is essential for individuals’ success. However, students face motivational barriers in online intercultural learning. Thus, this study aims to explore the effectiveness of integrating gamification with self-determination theory (SDT) to enhance the intrinsic motivation, ultimately aiding in the development of intercultural communication competence among Chinese vocational college students enrolled in online English intercultural learning. Employing a mixed-methods approach involving pre-post questionnaires and interviews, the study engaged 38 vocational college students from the automobile and rail transit faculty in a four-week online English intercultural learning module enriched with gamified elements such as points, badges, leaderboards, levels, and quests. The findings indicate that gamified learning effectively fulfills students’ needs for competence and autonomy, partially addressing their needs for relatedness and consequently fostering an upsurge in intrinsic motivation. Additionally, improvements were observed in knowledge, attitude, and skill, with marginal changes noted in awareness. It is concluded that gamified learning approaches based on SDT can positively contribute to the development of intrinsic motivation and intercultural communication competence. These findings hold practical implications for educational institutions and researchers to cultivate intrinsic motivation and ICC through online gamified learning.